One‐Pot UV‐Assisted Synthesis of Metal Phthalocyanine Nanocrystals. Issue 2 (21st March 2015) - Saito, Yuta; Higuchi, Takeshi; Sugimori, Hidekazu; Yabu, Hiroshi
Abstract: Metal phthalocyanines (PCs) are promising materials for various applications, including pigments, color filters, photovoltaic devices, and nonlinear optics, owing to their specific light‐absorption properties and high stability to chemical and thermal degradation. Nanocrystals (NCs) of metal PCs have received much attention because the optical and electronic properties of metal PCs are improved considerably by decreasing the crystal size to the nanoscale. In this study, we demonstrated the direct synthesis of Cu and Zn PCs in nanosized micelles by irradiating precursors with UV light. The synthesized metal PC NCs were stably dispersed in water by adding polyethylene glycol as a stabilizer. The aqueous dispersions of PC NCs showed strong visible light absorption from 500 to 800 nm and high transparency at wavelengths in the non‐absorption region. Abstract : One‐pot synthesis : A new strategy for direct synthesis of metal phthalocyanine nanocrystals from their precursors is reported based on a chemical reaction in nanosized micelles under UV irradiation. This method is universally applicable to prepare various metal phthalocyanines. The aqueous dispersions of metal phthalocyanine nanocrystals showed strong visible light absorption from 500 to 800 nm and high transparency at wavelengths in the non‐absorption region.